The Effectiveness of ADDIE-Based Negotiation Training among University Students - Tyas Nur Azalia; Naaila Firya; Elisa Maisarah; Zahra Putri Nuraisyah; Nathania Syakirah El-Bahri; Nayla Nur Arrahmah; Regina Herdiana Putri; Raska Rahma Niah; Iman Permana (Journal of Golden Generation Economic, 2025)
This study examines the effectiveness of an ADDIE-based negotiation training program implemented for university students from multiple institutions. Using a quantitative one-group pre-test–post-test design, the study evaluates whether the structured application of the ADDIE instructional design model leads to measurable improvements in negotiation skills. Data were collected through pre-training and post-training surveys and analyzed using a paired-samples t-test. The results indicate a statistically significant increase in participants’ post-test scores compared to pre-test scores, confirming the effectiveness of the training intervention. The findings further demonstrate that the systematic alignment of needs analysis, instructional design, material development, interactive implementation, and quantitative evaluation contributed to positive learning outcomes. This study contributes to the literature on instructional design and talent development by providing empirical evidence that ADDIE-based training can effectively enhance negotiation skills in higher education contexts.